High infectivity and unique genomic sequence characteristics of Cryptosporidium parvum in China. - Ruilian Jia; Wanyi Huang; Ni Huang; Zhengjie Yu; Na Li; Lihua Xiao; Yaoyu Feng; Yaqiong Guo (Public Library of Science (PLoS), 2022)
Zoonotic Cryptosporidium parvum infections are mainly caused by IIa and IId subtypes. As most biological characterizations have been performed on IIa subtypes, the biological and genetic characteristics of IId subtypes in China are not clear. We evaluated the infection and genetic characteristics of IId isolates in interferon-γ-knockout mice using qPCR to quantify oocyst shedding, histological examination to monitor pathological changes and comparative genomic analyses to identify infectivity and virulence-associated differences. Compared with the reference IIa isolate, mice infected with the IId isolates had significantly higher and longer oocyst shedding and lower body weight gain. In addition, the four IId isolates examined differed significantly in infectivity (as indicated by the median infective dose), oocyst shedding duration, and pathogenicity. Comparative genomic analysis indicated that the IId isolates had three more subtelomeric genes than the reference IIa isolate and 5385-5548 nucleotide substitutions, with the hypervariable genes mostly in two blocks on chromosome 1. In contrast, the four IId isolates differed from each other by 77-1,452 nucleotides, with virulence-associated sequence differences mainly in nine genes within a 28-kb block on chromosome 6. These data indicate the newly emerged C. parvum IId subtypes in China have high animal infectivity and unique genomic characteristics.